Factors related to quality of epidemiologic surveillance data (report from 506) from health centers in Muang district, Nakhonsithammarat province, Thailand - Sarote Teerakul (Chulalongkorn University, 2014)
Thesis (M.P.H.)--Chulalongkorn University, 2006